SOCIAL-PEDAGOGICAL PROBLEMS OF DEVELOPING COMMUNICATIVE CULTURE IN FUTURE SPECIALISTS - Asqarov Ixtiyor Baxtiyorovich; Xiloliddinova Feruza Rashidovna (International Scientific and Current Research Conferences, 2023)
This thesis explores the social-pedagogical problems associated with the development of communicative culture in future specialists. Effective communication skills are essential for professional success and societal integration. However, contemporary educational and social contexts present significant challenges in nurturing and enhancing communicative competence. This research delves into the multifaceted issues hindering the cultivation of adequate communicative culture, proposing strategies and recommendations to address these challenges and facilitate the development of proficient communicators in future specialists.